Promoting Studentsâ Listening Comprehension through Online Peer-Correction - Rozak, Refi Ranto (Sebelas Maret University, 2016)
Listening practices have widely been conducted face to face in language laboratory for years in language laboratory. However, studentsâ interaction and collaboration were not much emphasized because of teacher-centred learning. The teaching of listening in language laboratory focuses primarily on how to answer comprehension questions correctly without any interactive discussion. Students just relied on teacherâs absolute role in language laboratory. Thus, the students were not independent in learning listening. Meanwhile, limited materials used in listening instruction are mostly influenced by teacher educatorâs textbooks whose content lacked of authenticity. Promoting online learning in listening practices and evaluating studentsâ outcomes through peer-corrective feedback through learning platform were needed to enhance their comprehension. This article highlighted five central issues, including: (1) theoritical framework of online learning; (2) edmodo as a learning platform for online mediated listening tool; (3) the selection of authentic listening materials; (4) peer-collaborative correction in listening tasks; and (5) the development of studentsâ autonomous listening through online corrective feedbacks. The impacts of this article findings successfully contributed to support teachersâ educators face-to-face language laboratory based listening practices while promoting studentsâ collaboration, autonomy, and comprehension.Â